The awareness and accessibility of village official website on marginalized villagers in Central Java Indonesia / Nuryanti ... [et al.] - -, Nuryanti; -, Subejo; Witjaksono, Roso; Fathoni, Mochamad (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
The emergence of village official website as a new village community empowering media brings its own consequence and impact. Village government as a part of empowering actor is obliged to open awareness and accessibility of information for villagers through village official website. In fact, there are some limitations causing particular villagers to be marginalized. By applying qualitative method, through the in-depth interview with the marginalized villagers, and focus group discussion with the village apparatus, the villagers and empowerment actors. This research seeks to analyze the awareness and accessibility of information for marginalized villagers in Susukan Village, Sumbang Subdistrict, Banyumas District, Central Java. Research findings showed that awareness and accessibility of information for marginalized villagers in Susukan Village is still considerably limited because of low educational and high resistence level regarding internet. Thus, appropriate approach and well-designed information in village official website are highly recommended in order that villagers can optimally access and utilize village official website for supporting their daily socio-economic activities. Furthermore, this research is expected to be a material evaluation of the government in implementing village information system policies and give more attention to marginalized villagers regarding their ability to access information from village official website.